1988
DOI: 10.1111/j.1540-8159.1988.tb03965.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Low Threshold Platinized Epicardial Pacing Electrode: Comparative Evaluation in Immature Canines

Abstract: A prospective comparison of pacing and sensing capabilities between the conventional Medtronic Model 4951 platinum-iridium epicardial pacing electrode and a new modified "platinized" version of the same electrode was performed in immature canines to determine if the new electrode design improves pacing in the immature myocardium. The conventional electrode was modified by electroplating platinum black particles onto the surface to increase the effective or true microscopic surface area, yet essentially maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…For example, it has long been known that a perfectly clean electrode will produce a lower stimulation threshold than one contaminated with dust, fiber, glove powder, or other contaminants collected during the lead's manufacture or implantation. Thoroughly cleaned platinized platinum epicardial leads have demonstrated superior stimulation thresholds and reduced fibrotic tissue encapsulation in immature canines . A variation of the clean electrode concept was the Nafion® copolymer ion‐exchange membrane (DuPont, Wilmington, DE, USA), which allows a free flow of current.…”
Section: The Influence Of Electrode Design At the Electrode‐tissue Inmentioning
confidence: 99%
“…For example, it has long been known that a perfectly clean electrode will produce a lower stimulation threshold than one contaminated with dust, fiber, glove powder, or other contaminants collected during the lead's manufacture or implantation. Thoroughly cleaned platinized platinum epicardial leads have demonstrated superior stimulation thresholds and reduced fibrotic tissue encapsulation in immature canines . A variation of the clean electrode concept was the Nafion® copolymer ion‐exchange membrane (DuPont, Wilmington, DE, USA), which allows a free flow of current.…”
Section: The Influence Of Electrode Design At the Electrode‐tissue Inmentioning
confidence: 99%
“…Pacing impedance varies as a function of the geometric surface area of electrode, however, the source impedance varies as a function of the microscopic surface area of the electrode 3 . Several designs have been developed to create a large microscopic surface area: a porous electrode was made by coiled wire mesh with a basket screen (groups I and III) while the platinized electrode was made by a microporous surface (group II) 1–3 . These designs have resulted in a small geometric surface area, high impedance, steroid‐eluting electrode with a larger electrode‐tissue contact area to improve sensing and to facilitate tissue ingrowth for prevention of electrode dislodgement.…”
Section: Discussionmentioning
confidence: 99%
“…It appeared that the electrode tissue interface reaction play an important role during long‐term electrical performance, as the changes during long‐term follow‐up were similar in groups with same electrode material (groups I and III) regardless of tip electrode geometric surface area. Previous canine histological study has demonstrated that the inflammatory response could be minimized by modification of the electrode surface to an ultrasmall particulate surface, resulting in a thinner fibrotic capsule and lower chronic threshold 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation